Analisis Kandungan Total Fenolik, Flavonoid dan Aktivitas Antioksidan Ekstrak Etanol, Fraksi Syzygium cumini (L) Skells. - Himyatul Hidayah; Surya Amal; Rifah Alena Rades (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The stem bark of Syzygium cumini (L.) Skeels is known to contain secondary metabolites, particularly phenolic and flavonoid compounds, which function as natural antioxidants by donating hydrogen atoms or electrons to neutralize free radicals, thereby protecting cells from oxidative stress-induced damage. This study aimed to evaluate the total phenolic content, total flavonoid content, and antioxidant activity of the ethanol extract and solvent fractions of S. cumini stem bark. Total phenolic content was determined using the Folin–Ciocalteu method, while total flavonoid content was quantified using the aluminum chloride (AlCl₃) colorimetric assay. Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The results demonstrated that the ethanol extract contained a total phenolic content of 37.41 mg gallic acid equivalents (GAE)/g extract and a total flavonoid content of 29.94 mg quercetin equivalents (QE)/g extract. The antioxidant activity assay revealed that the ethanol extract, n-hexane fraction, and ethyl acetate fraction exhibited IC₅₀ values of 12.30, 92.82, and 21.72 µg/mL, respectively. According to the antioxidant activity classification, the ethanol extract and ethyl acetate fraction exhibited very strong antioxidant activity, whereas the n-hexane fraction showed strong antioxidant activity.